2015
DOI: 10.1371/journal.pone.0119935
|View full text |Cite
|
Sign up to set email alerts
|

C:N:P Stoichiometry and Leaf Traits of Halophytes in an Arid Saline Environment, Northwest China

Abstract: Salinization is an important and increasingly prevalent issue which has broad and profound effects on plant survival and distribution pattern. To understand the patterns and potential drivers of leaf traits in saline environments, we determined the soil properties, leaf morphological traits (specific leaf area, SLA, and leaf dry matter content, LDMC), leaf chemical traits (leaf carbon, C, nitrogen, N, and phosphorus, P, stoichiometry) based on 142 observations collected from 23 sites in an arid saline environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
74
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 57 publications
13
74
8
Order By: Relevance
“…Comparison of our results with those of other studies in which samples were collected in July or July-August revealed that the leaf C:N ratios of all larch stands were higher than those of the arid saline biomes of China (15.7 ± 5.6) [24] and the global value (23.8 ± 17.3) [25,26]. Furthermore, the leaf C:P ratios were higher than those of the arid saline biomes of China (229.4 ± 63.7) [24] but lower than the global value (300.9 ± 236.8) [25,26].…”
Section: Patterns Of Leaf C:n:p Stoichiometric Ratios Across All Diffsupporting
confidence: 71%
See 2 more Smart Citations
“…Comparison of our results with those of other studies in which samples were collected in July or July-August revealed that the leaf C:N ratios of all larch stands were higher than those of the arid saline biomes of China (15.7 ± 5.6) [24] and the global value (23.8 ± 17.3) [25,26]. Furthermore, the leaf C:P ratios were higher than those of the arid saline biomes of China (229.4 ± 63.7) [24] but lower than the global value (300.9 ± 236.8) [25,26].…”
Section: Patterns Of Leaf C:n:p Stoichiometric Ratios Across All Diffsupporting
confidence: 71%
“…Furthermore, the leaf C:P ratios were higher than those of the arid saline biomes of China (229.4 ± 63.7) [24] but lower than the global value (300.9 ± 236.8) [25,26]. In addition, the leaf N:P ratios were lower than those of Chinese flora (16.3 ± 9.3) [18], the arid saline flora of China (15.4 ± 3.7) [24], the desert flora of northern China (15.77 ± 7.5) [27] and the global value (13.8 ± 9.5) [25,26] (Table 5 and Table S3). The differences in the leaf C:N, C:P and N:P ratios among different studies are likely due to differences in ecosystem type, sampling time, abiotic factors (such as temperature, elevation, precipitation, and drought) [25] and biological factors [26].…”
Section: Patterns Of Leaf C:n:p Stoichiometric Ratios Across All Diffmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, one study also suggested that what drove the variation in halophytes leaf N:P stoichiometry was the available nutrients in the soil rather than the salt concentration (Wang et al . ). Saline stress can also reduce the accumulation of K, Ca and Mg, as well as K:Na ratio in leaves, while increasing Na in some experiments (Khan et al .…”
Section: Introductionmentioning
confidence: 97%
“…Indeed, chemical elements are the basic principles of stoichiometry5. Leaf shape and plant size are key aspects of plant morphological performance, which can provide general information about plant growth and investment strategies34. Therefore, it is imperative to explore the relationships between leaf stoichiometry and leaf shape and plant size.…”
mentioning
confidence: 99%